Trend Jual Beli Online Melalui Situs Resmi Menurut Tinjauan Etika Bisnis Islam - Sriwahyuni, Eka (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2019)
This paper the trends of buying and selling online through sites in terms of the perspective of Islamic business ethics. This research uses the method of library research (research literature) that is research whose source of information is from various library materials by reading and studying books and writings that have objects with discussion. The results showed that in Indonesia there are various online buying and selling sites, with a very rapid marketplace development in Indonesia. There are many marketplace sites such as Open Stalls, Pedia Stores, OLX, Lazada, Elevenia and others. But the most visited marketplace site today is the Shopee marketplace site. An overview of Islamic business ethics of buying and selling online is permissible as long as the items being traded are in accordance with the appearance of the goods and specifications in the description of the online store. In buying and selling online on the shopee site already meets the applicable requirements in accordance with the appearance and description (specifications of goods) on the storefronts that are extended in the online shop on the shopee site.